Розробка та оптимізація ігрової програми на базі операційної системи вбудованих інформаційно-комунікаційних систем для пристрою Raspberry Pi - Бухтіяров, Є. Є. (ХНУРЕ, 2025)
A game development and optimization system is a crucial tool for creating efficient and interactive applications on embedded platforms such as Raspberry Pi. This paper explores the development of a snake game based on the Pygame library, running on an embedded operating system. The project is implemented using Python and focuses on optimizing graphics rendering, input handling, and resource management. The system ensures smooth gameplay by efficiently processing user input, managing frame rates, and dynamically updating the game environment.
Keywords: оптимізація ігрової програми; Raspberry Pi